Phytochemical Constituents and Therapeutic Potential of Pine Bark and Needle Extracts in Cardiovascular and Metabolic Disorders - Muhammad Ainur Rosyid Ridho; Ratri Dwi Indriani; Arfiana Tanti Wulansari; Kristanti Indah Purwani; Tutik Nurhidayati; Veranita Aprilia; Anindhita Nabilah Pradani; Roy Ardiansyah Putra; Ardiansyah Farid (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2026)
Cardiovascular and metabolic diseases remain leading global health challenges, necessitating novel and complementary therapeutic strategies. Natural plant-derived compounds, particularly from pine bark and needles, have attracted attention for their potential health benefits. This study aims to comprehensively review the phytochemical composition of pine bark and needle extracts, focusing on their biological activities and potential roles in preventing and managing cardiovascular and metabolic disorders. A literature review was conducted using databases such as PubMed, ScienceDirect, and Google Scholar, focusing on studies published from 2000 to 2024. The selection criteria included in vitro, in vivo, and clinical research articles investigating the phytochemical profiles and pharmacological effects of pine bark and needle extracts on cardiovascular and metabolic health. Pine bark and needle extracts, especially from Pinus pinaster, are rich in proanthocyanidins, flavonoids, phenolic acids, stilbenes, and terpenoids. These bioactive compounds exhibit potent antioxidant, anti-inflammatory, and endothelial protective properties. Clinical and preclinical studies demonstrate improvements in blood pressure, lipid profiles, glucose metabolism, and vascular function. Emerging evidence also suggests a role in modulating gut microbiota, contributing to systemic metabolic benefits. Pine bark and needle extracts hold significant promise as adjunct therapies for cardiovascular and metabolic diseases through their multi-targeted mechanisms. Further well-designed clinical trials are necessary to validate their efficacy, optimize dosages, and ensure safety for broader therapeutic application.